ANALISIS PEMASARAN BUAH STRAWBERRY DI KECAMATAN DANAU MAS HARUN BASTARI KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Riski Ageng Cahyomi; Dwita Prisdinawati; Mira Yanuarti (Lembaga Pengembangan Kinerja Dosen, 2022)
The research analysis of Strawberry Fruit Marketing in the Lake Mas Harun Bastari area, Selupu Rejang District, Rejang Lebong Regency aims to find out marketing channels, marketing margins, and to find out how efficient the Strawberry marketing is in the Danau Mas Harun Bastari tourism area. This research was conducted in June 2022 in the area of ​​Danau Mas Harun Bastari, Selupu Rejang District, Rejang Lebong Regency with farmers and traders in the Mas Harun Bastari Lake area. The data analysis used in this research is Marketing Channel Analysis, Marketing Margin Analysis, and Marketing Efficiency Analysis. This data analysis was used for Farmers and the 11 Retailers Respondents in the Danau Mas Harun Bastari District, Selupu Rejang District, Rejang Lebong Regency. Based on this research, it is known that the Strawberry Marketing Channel in Selupu Rejang District, Rejang Lebong Regency has one Marketing Channel. Where farmers (producers) sell directly to retailers, then retailers sell to consumers at a price of Rp. 60,000 with a 0.5 kg mica box at a price of Rp. 35,000 and 0.25 kg at a price of Rp. 25,000 where the cost of Rp. 60,000/Kg will get profit of IDR 30,000/kg. This value explains that the retailer receives a higher price than the price received by the consumer, which means that the retailer is not disadvantaged in the marketing channel because the profits obtained by the retailer are greater than the marketing institutions in the marketing channel. The costs incurred by Retailers are in the form of transportation costs, packaging costs, equipment depreciation costs. because the strawberries are well sorted to suit the wishes of consumers. The advantage of marketing institutions is in the form of remuneration received by each marketing agency that participates in marketing strawberries starting from the Farmer level to the Consumer level.